Insan Kamil Dalam Pemikiran Abdul Karim Al-Jili - Nabilla Ramadayanti Latifah (Program Studi Aqidah dan Filsafat Islam STISA Ash-Shofa Tasikmalaya, 2026)
The concept of al-insan al-kamil (the perfect human) is the core of the metaphysical Sufi thought of Abdul Karim Al-Jili (d. 805 H), a Sufi figure who was greatly influenced by the teachings of Ibn Arabi. For Al-Jīlī, the perfect human is the most complete manifestation of the tajalli (appearance) of God's attributes and names that exist in humans. Insan al-kamil not only achieves moral and spiritual perfection, but also reflects the wholeness of existence because in him the essence of the beginning and the end, the outer and the inner, and the universe as a microcosm are gathered. In Al-Jili's view, the peak of this perfection is fully realized in the Prophet Muhammad as the highest prototype of the perfect human, while the saints and those who achieve true closeness to God are only reflections of the essence of the Prophet Muhammad. Al-Jili's thoughts on human perfection provide a foundation for Sufi spirituality that emphasizes the integration of the divine and human dimensions. The relevance of this concept can still be felt in modern life, particularly as a transformative paradigm offering to build spiritual, ethical, and humanistic awareness amidst the contemporary humanitarian crisis.